Polarizer protective film, polarizing plate and liquid crystal display device
By controlling the angle of heat shrinkage in polyester films used as polarizer protective films, the issue of light leakage in liquid crystal display devices is addressed, enhancing visibility and image quality.
Patent Information
- Application Number
- JP2022072042
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2013-09-10
- Filing Date
- 2022-04-26
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2034-09-05
AI Technical Summary
The use of polyester films as polarizer protective films in liquid crystal display devices can lead to light leakage when polarizers are arranged in a cross-Nicol relationship, resulting in reduced visibility and image quality due to optical distortion.
A polarizer protective film made of a polyester film where the absolute value of the angle between the film flow or width direction and the direction of the maximum heat shrinkage rate is 15 degrees or less, with specific retardation, Nz coefficient, and surface orientation values to minimize light leakage and optical distortion.
The solution effectively suppresses light leakage and improves visibility in liquid crystal display devices by maintaining high durability and optical quality, even when polarizers are arranged in a cross-Nicol relationship.
Smart Images

Figure 0007669314000003 
Figure 0007669314000004 
Figure 0007669314000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizer protective film used for a polarizing plate in a liquid crystal display device. [Background technology]
[0002] Polarizing plates used in liquid crystal displays (LCDs) are usually constructed by sandwiching a polarizer made of polyvinyl alcohol (PVA) or the like dyed with iodine between two polarizer protective films, and triacetyl cellulose (TAC) films are usually used as polarizer protective films. In recent years, as LCDs become thinner, there has been a demand for thinner polarizing plates. However, when the thickness of the TAC film used as a protective film is reduced for this purpose, problems arise in that sufficient mechanical strength cannot be obtained and moisture permeability deteriorates. In addition, TAC films are very expensive, and there is a strong demand for cheaper alternative materials.
[0003] In view of this, in order to reduce the thickness of the polarizing plate, it has been proposed to use a polyester film instead of the TAC film so that the polarizer protective film can maintain high durability even if it is thin (Patent Documents 1 to 3).
[0004] Polyester films are more durable than TAC films, but unlike TAC films, they have birefringence, and therefore when used as a polarizer protective film, there is a problem that image quality is degraded due to optical distortion. That is, since polyester films having birefringence have a certain optical anisotropy (retardation), when used as a polarizer protective film, rainbow-like color spots are generated when observed from an oblique direction, and image quality is degraded. For this reason, in Patent Documents 1 to 3, measures are taken to reduce retardation by using copolymer polyester as the polyester.
[0005] Furthermore, Patent Document 4 discloses that rainbow-like color unevenness can be solved by using white light-emitting diodes as a backlight source and further using an oriented polyester film having a certain retardation as a polarizer protective film.
[0006] Patent Document 5 discloses that since a polarizer protective film undergoes many heat treatment steps, such as during the production of a polarizing plate or during a step of combining the obtained polarizing plate with a liquid crystal cell, it has good dimensional stability; specifically, it is preferable that the shrinkage rate of a polyester film after unconstrained heat treatment at 120°C for 30 minutes is 5% or less in both the MD and TD directions of the film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2002-116320 A [Patent Document 2] JP 2004-219620 A [Patent Document 3] JP 2004-205773 A [Patent Document 4] WO2011-162198 [Patent Document 5] JP 2010-277028 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, the polyester film used as the polarizer protective film has been improved from various viewpoints, but the present inventors have found that there is room for further improvement. That is, the present inventors have found that the polyester film improved so far can be used as the polarizer protective film. In the past, a new problem was found in that when a polarizing plate used as a polarizer is arranged in a crossed Nicol relationship with another polarizing plate, slight light leakage occurs, resulting in poor visibility. Therefore, an object of the present invention is to provide a polarizer protective film made of a polyester film that can suppress the above-mentioned slight light leakage. [Means for solving the problem]
[0009] As a result of intensive research by the present inventors to solve the above problems, they found that the above problems can be solved by controlling the absolute value of the angle between the direction in which the heat shrinkage rate of the polyester film is maximum and the machine direction or width direction of the polyester film (i.e., the inclination of the direction in which the heat shrinkage rate is maximum with respect to the machine direction or width direction of the film) to 15 degrees or less. Based on this finding, further research was conducted, and the following representative inventions are provided. Section 1. A polarizer protective film which is a polyester film in which the absolute value of the angle between the film flow direction or width direction and the direction in which the thermal shrinkage rate of the film is maximum is 15 degrees or less. Section 2. Item 2. A polarizer protective film according to item 1, wherein the polyester film has a retardation of 4,000 to 30,000 nm and an Nz coefficient of 1.7 or less. Section 3. 3. The polarizer protective film according to item 1 or 2, wherein the polyester film has a degree of planar orientation of 0.13 or less. Section 4. The polarizer protective film is laminated on both sides of the polarizer. Item 4. A polarizing plate, at least one of which has a polarizer protective film which is the polarizer protective film according to any one of items 1 to 3. Section 5. A polarizing plate comprising the polarizer protective film according to any one of items 1 to 3 laminated on one side of a polarizer. Section 6. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, the backlight light source is a white light source having a continuous emission spectrum; The polarizing plate has a structure in which a polarizer protective film is laminated on both sides of a polarizer, A liquid crystal display device, wherein at least one of a polarizer protective film of a polarizing plate arranged on an incident light side and at least one of a polarizer protective film of a polarizing plate arranged on an exit light side is the polarizer protective film according to any one of items 1 to 3. Section 7. Item 7. The liquid crystal display device according to item 6, wherein a polarizer protective film on an incident light side of a polarizing plate arranged on the incident light side and a polarizer protective film on an exit light side of a polarizing plate arranged on the exit light side are the polarizer protective films according to any one of items 1 to 3. Section 8. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, the backlight light source is a white light source having a continuous emission spectrum; Item 6. A liquid crystal display device, wherein the polarizing plate is the polarizing plate according to item 5. Effect of the Invention
[0010] According to the present invention, when two polarizing plates are arranged in a crossed Nicol relationship, it is possible to suppress the slight light leakage that occurs conventionally. Also, according to a preferred embodiment, it is possible to provide a liquid crystal display device that is suitable for thinning, does not produce rainbow spots, and has excellent visibility in which the deterioration of visibility caused by the light leakage is reduced. [Brief description of the drawings]
[0011] [Figure 1] Figure 1 shows an example of the results of measuring the thermal shrinkage of a film over 360 degrees at 5 degree intervals, with the machine direction of the film being 0 degree. In this example, the angle at which the thermal shrinkage is maximum is approximately 15 degrees. [Diagram 2] FIG. 2 is a plot of angle on the X-axis and heat shrinkage on the Y-axis to determine the angle at which the heat shrinkage is maximum with an accuracy of 1 degree or higher from the heat shrinkage measured at 5 degree intervals. [Diagram 3]FIG. 3 shows a schematic diagram of the intervals between clips used in Method 1 for reducing the slope of the thermal shrinkage rate. [Figure 4] FIG. 4 shows the relationship between the distance in the tenter longitudinal direction and the tenter temperature that can be used in Method 4 for reducing the slope of the thermal shrinkage rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] 1. Polarizer protection film The polarizer protective film of the present invention is a polyester film, and the absolute value of the gradient of the direction in which the thermal shrinkage rate is maximum with respect to the machine direction or width direction of the film (hereinafter, sometimes simply referred to as the gradient of the thermal shrinkage rate) is preferably 15 degrees or less. The absolute value of the gradient of the thermal shrinkage rate is preferably 12 degrees or less, more preferably 10 degrees or less, even more preferably 8 degrees or less, even more preferably 6 degrees or less, particularly preferably 4 degrees or less, and most preferably 2 degrees or less. The smaller the absolute value of the gradient of the thermal shrinkage rate, the more preferable it is, and therefore the lower limit is 0 degrees.
[0013] Although the exact mechanism by which the slight light leakage occurs has not been elucidated, it is believed to be as follows. In a liquid crystal display device, two polarizing plates are usually arranged in a crossed Nicol relationship. When two polarizing plates are arranged in a crossed Nicol relationship, light does not usually pass through the two polarizing plates. However, when the polarizer protective film shrinks due to heat treatment, the polarizer also shrinks or warps slightly accordingly, and as a result, the complete crossed Nicol relationship is broken, and light leaks. Based on this principle, light leakage becomes significant when the direction in which the thermal shrinkage rate of the polarizer protective film is the largest is an oblique direction to the film flow direction or film width direction. The flow direction of the polarizer protective film is usually parallel or perpendicular to the polarization axis of the polarizer.
[0014] Patent Document 5 discloses a polarizer protective film made of a polyester film having a heat shrinkage rate of 5% or less in both the MD and TD directions. However, as is clear from the above-mentioned mechanism, even if the heat shrinkage rate in the MD and TD directions is small, the problem of leakage of polarized light occurs when the direction in which the heat shrinkage rate is maximum is inclined relative to the film flow direction or the film width direction.
[0015] Patent Document 5 also discloses that the angle between the in-plane slow axis of the film and the TD direction of the film and the variation therein are reduced for both ends of the film to prevent color shift and color spots in liquid crystal displays. However, since the direction of the in-plane slow axis of the film and the gradient of the thermal shrinkage rate are not necessarily parallel, the problem of leakage of polarized light occurs even if the film has a controlled in-plane slow axis.
[0016] The polyester film used in the polarizer protective film of the present invention can be obtained from any polyester resin. The type of polyester resin is not particularly limited, and any polyester resin obtained by condensing a dicarboxylic acid and a diol can be used.
[0017] Dicarboxylic acid components that can be used in the production of polyester resins include, for example, terephthalic acid. Acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, dodecadicarboxylic acid, and the like.
[0018] Examples of diol components that can be used in producing polyester resins include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0019] The dicarboxylic acid component and the diol component constituting the polyester resin can be used alone or in combination. Suitable polyester resins constituting the polyester film include, for example, polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and more preferably polyethylene terephthalate and polyethylene naphthalate, which may further contain other copolymerization components. These resins are excellent in transparency and thermal and mechanical properties, and retardation can be easily controlled by stretching. In particular, polyethylene terephthalate is the most suitable material because it has a large inherent birefringence and can relatively easily obtain a large retardation even if the film is thin.
[0020] (Heat shrinkage rate) The heat shrinkage of the polyester film is preferably 5% or less in all directions. The heat shrinkage of the polyester film in all directions is measured as follows.
[0021] The polyester film is cut into a square shape with sides of 21 cm, and left in an atmosphere of 23°C and 65% RH for at least 2 hours. A circle with a diameter of 80 mm is drawn on the polyester film with the center at the center, and the diameter is measured at 5 degree intervals using a two-dimensional image measuring device (e.g., QUICK IMAGE made by MITUTOYO), with the film flow direction set to 0 degrees. Here, the film flow direction is set to 0 degrees, and clockwise (right-handed) is set to a positive angle when the film is viewed from above in the tenter, and counterclockwise (left-handed) is set to a negative angle. If the measurement is made in the range of -90 degrees to 85 degrees, the diameter in all directions can be measured.
[0022] Next, the polyester film is heat-treated in water at 85°C for 30 minutes, the moisture on the film surface is wiped off, it is air-dried, and then it is left in an atmosphere of 23°C and 65% RH for at least 2 hours. Then, the diameter of the circle is measured at 5 degree intervals in the same manner as above. The diameter before heat treatment is Lo, and the diameter in the same direction after heat treatment is L, and the thermal shrinkage in each direction is calculated according to the following formula. .
[0023] Heat shrinkage rate (%) = ((L0- L) / L0) x 100
[0024] When the heat shrinkage measured over 360 degrees at 5 degree intervals is plotted on a graph, it looks like Figure 1, for example. In Figure 1, the center of the circle indicates 0% heat shrinkage, and the heat shrinkage increases as the distance from the center of the circle increases. The circumference also indicates the angle with the film flow direction being 0 degrees. Therefore, 90 degrees is parallel to the film width direction.
[0025] The heat shrinkage rate determined by the above-mentioned measuring method is preferably 5% or less, more preferably 3% or less, even more preferably 1% or less, and most preferably 0.5% or less. The lower limit of the heat shrinkage rate is not particularly limited, but is, for example, 0.01% or more.
[0026] (Thermal shrinkage rate gradient) As described above, the heat shrinkage is measured at 5 degree intervals, but the direction in which the heat shrinkage is maximum can be found with an accuracy of 1 degree by following the procedure below. That is, the heat shrinkage measurement results (heat shrinkage results in the range of -90 degrees to 85 degrees) are plotted as shown in Figure 2, with the horizontal axis representing the angle with the film flow direction at 0 degrees, and the vertical axis representing the heat shrinkage at that angle. At this time, values from -180 degrees to -95 degrees and from 90 degrees to 175 degrees are also interpolated (the heat shrinkage at -90 degrees corresponds to the heat shrinkage at 90 degrees). (The thermal shrinkage at 0° corresponds to the thermal shrinkage at -180°). Next, we draw an approximate curve connecting each plot. A line is drawn, and the direction in which the thermal shrinkage rate is maximum is read with an accuracy of 1 degree, and this is defined as α. , -90 degrees≦α≦90 degrees.
[0027] When the direction α in which the thermal shrinkage rate is maximum is in the range of -45 degrees to 45 degrees, that value is taken as the gradient of the thermal shrinkage rate. When the direction α in which the thermal shrinkage rate is maximum is 45 degrees or more or -45 degrees or less, it is interpreted as being gradient based on the film width direction, not the film flow direction, and the gradient of the thermal shrinkage rate is α-90 degrees (when α is 45 degrees or more) or 90 degrees + α (when α is -45 degrees or less). When the difference between the maximum and minimum values of the thermal shrinkage rate is 0.1% or less, the thermal shrinkage rate is in all directions. Since the thermal shrinkage rates are almost equal and there is no gradient in the thermal shrinkage rate, the gradient in the thermal shrinkage rate is regarded as 0 degrees.
[0028] (Light leakage evaluation method) The light leakage is measured by arranging two polarizing plates in a crossed Nicol relationship and measuring the maximum transmittance of light with a wavelength of 550 nm to 600 nm that passes through them. The light transmittance can be measured using any spectrophotometer. The measured maximum transmittance is preferably 0.02% or less, and more preferably 0.015% or less.
[0029] Next, from the viewpoint of suppressing rainbow spots, the retardation, Nz coefficient, and degree of planar orientation of the polyester film will be described.
[0030] (Retardation) The polyester film used in the polarizer protective film preferably has a retardation of 4000 to 30000 nm. If the retardation is 4000 nm or more, rainbow spots that may occur when the liquid crystal display device is observed from an oblique direction are suppressed, and good visibility can be ensured. The preferred retardation of the polyester film is 4500 nm or more, more preferably 5000 nm or more, even more preferably 6000 nm or more, even more preferably 8000 nm or more, and even more preferably 10000 nm or more. Here, 4000 to 30000 nm means that the lower limit is 4000 nm and the upper limit is 30000 nm, but a range that does not include these is also assumed.
[0031] The upper limit of the retardation of the polyester film is not particularly limited, but is, for example, 30,000 nm. Even if a polyester film having a retardation higher than this is used, the effect of further improving visibility is not substantially obtained, and the thickness of the film increases considerably with an increase in retardation, which may deteriorate the handleability as an industrial material.
[0032] The retardation value of an oriented polyester film can be obtained by the following procedure. The orientation axis direction of the film is determined using a molecular orientation meter (e.g., MOA-6004 molecular orientation meter manufactured by Oji Measurement Instruments Co., Ltd.). The refractive index (ny) in the orientation axis direction and the refractive index (ny) perpendicular to the orientation axis direction and in the film plane are calculated. The refractive index (nx) in the intersecting direction is measured at a measurement wavelength of 589 nm. The absolute value (|ny-nx|) of the difference (anisotropy) in the refractive index in these two axial directions is calculated, and the retardation value is calculated by multiplying it by the thickness of the film. The retardation of the film can be measured using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.). The refractive index of the film can also be measured using a commercially available measuring device such as an Abbe refractometer (Atago Co., Ltd., NAR-4T).
[0033] (Nz coefficient) The polyester film used for the polarizer protective film is preferably within the above-mentioned retardation range and has an Nz coefficient represented by |ny-nz| / |ny-nx| of 1.7 or less. The Nz coefficient can be calculated as follows. The orientation axis direction of the film is calculated using a molecular orientation meter (MOA-6004 type molecular orientation meter manufactured by Oji Measurement Instruments Co., Ltd.), and the biaxial refractive index (ny, nx, where ny>nx) of the orientation axis direction and the direction perpendicular thereto, and the refractive index (nz) in the thickness direction are calculated using an Abbe refractometer (NAR-4T manufactured by Atago Co., Ltd., measuring wavelength 589 nm). The thus calculated nx, ny, and nz can be substituted into the formula represented by |ny-nz| / |ny-nx| to calculate the Nz coefficient.
[0034] Even if the retardation of the polyester film is 4000nm to 30000nm, if the Nz coefficient exceeds 1.7, when the polyester film is used as a polarizer protective film in both of a pair of polarizing plates (for example, when the polarizer protective film on the incident light side of the polarizing plate arranged on the incident light side and the polarizer protective film on the outgoing light side of the polarizing plate arranged on the outgoing light side are polyester films), rainbow spots may still occur depending on the angle when the liquid crystal display device is observed from an oblique direction. From the viewpoint of suppressing the occurrence of such rainbow spots, the Nz coefficient is more preferably 1.65 or less, and even more preferably 1.63 or less. The lower limit of the Nz coefficient is 1.2. This is because it is technically difficult to obtain a film with an Nz coefficient of less than 1.2. In order to maintain the mechanical strength of the film, the lower limit of the Nz coefficient is preferably 1.3 or more, more preferably 1.4 or more, and even more preferably 1.45 or more.
[0035] (Face orientation coefficient) In addition to controlling the retardation value and Nz coefficient of the polyester film within the above specific range, by setting the plane orientation coefficient represented by (nx+ny) / 2-nz to a specific value or less, it is possible to more reliably eliminate rainbow spots when a polyester film is used as a polarizer protective film for both of a pair of polarizing plates. Here, the values of nx, ny, and nz are determined in the same manner as the Nz coefficient. The plane orientation degree of the oriented polyester film is preferably 0.13 or less, more preferably 0.125 or less, and even more preferably 0.12 or less. By setting the plane orientation degree to 0.13 or less, it is possible to completely eliminate rainbow spots observed depending on the angle when the liquid crystal display device is observed from an oblique direction. The plane orientation degree is preferably 0.08 or more, more preferably 0.1 or more. If the plane orientation degree is less than 0.08, the film thickness may vary, and the retardation value may become non-uniform within the film plane.
[0036] (retardation ratio) The ratio (Re / Rth) of the retardation (Re) to the retardation in the thickness direction (Rth) of the polyester film is preferably 0.2 or more, more preferably 0.5 or more, and even more preferably 0.6 or more. The larger the ratio (Re / Rth) of the retardation to the retardation in the thickness direction (Rth), the more isotropic the birefringence action becomes, and the less likely it is that rainbow-like color spots will occur depending on the observation angle. In a completely uniaxial (symmetrical) film, the ratio (Re / Rth) of the retardation to the retardation in the thickness direction is 2. However, as described later, the closer to a completely uniaxial (symmetrical) film, the greater the mechanical strength in the direction perpendicular to the orientation direction. Therefore, the retardation and the retardation in the thickness direction are adjusted to 0.2 or more. The upper limit of the ratio (Re / Rth) is preferably 1.2 or less, and more preferably 1 or less. In order to completely suppress the occurrence of rainbow-like color spots due to the observation angle, the ratio (Re / Rth) of the retardation to the retardation in the thickness direction does not need to be 2, and 1.2 or less is sufficient. Even if the ratio is 1.0 or less, it is still possible to satisfy the viewing angle characteristics required for a liquid crystal display device (approximately 180 degrees left and right, and 120 degrees up and down).
[0037] (Thickness unevenness) In order to suppress the fluctuation of the retardation of the polyester film, it is preferable that the thickness unevenness of the film is small. From this viewpoint, the thickness unevenness of the polyester film is preferably 5% or less, more preferably 4.5% or less, even more preferably 4% or less, and particularly preferably 3% or less. The thickness unevenness of the film can be measured by the following procedure. A film is cut out in the TD direction from the film roll to a width of 40 mm. The thickness of the cut out sample in the TD direction is continuously measured using an Anritsu contact type continuous thickness meter (feed speed: 1.5 m / min, sampling period: 100 ms), and the average, maximum and minimum values are measured. The thickness unevenness was calculated using the following formula and the absolute value was used. Thickness unevenness = ((maximum measurement result) - (minimum measurement result)) / (average measurement result) x 1 00(%)
[0038] (film thickness) The thickness of the polyester film is not particularly limited, but is usually 15 to 300 μm, and preferably 15 to 200 μm. If the film thickness is less than 15 μm, the anisotropy of the mechanical properties of the film becomes significant, and tearing, breaking, etc. may occur. A particularly preferred lower limit of the thickness is 25 μm. On the other hand, if the upper limit of the thickness of the polarizer protective film exceeds 300 μm, the thickness of the polarizing plate becomes too thick, which is not preferred. From the viewpoint of practicality as a polarizer protective film, the upper limit of the thickness is preferably 200 μm. A particularly preferred upper limit of the thickness is 100 μm, which is approximately the same as that of a general TAC film.
[0039] (light transmittance) From the viewpoint of suppressing deterioration of the optically functional dye such as iodine dye contained in the polarizer, the polyester film desirably has a light transmittance of 20% or less at a wavelength of 380 nm. The light transmittance of 380 nm is more preferably 15% or less, further preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, deterioration of the optically functional dye caused by ultraviolet rays can be suppressed. The light transmittance is measured perpendicular to the plane of the film, and can be measured using a spectrophotometer (for example, a spectrophotometer V-7100 manufactured by JASCO Corporation).
[0040] The transmittance of the oriented polyester film at a wavelength of 380 nm can be controlled to 20% or less by appropriately adjusting the type and concentration of the ultraviolet absorbent to be blended and the thickness of the film. The ultraviolet absorbent used in the present invention can be appropriately selected from known ultraviolet absorbents. Specific examples of the ultraviolet absorbent include organic ultraviolet absorbents and inorganic ultraviolet absorbents, and organic ultraviolet absorbents are preferred from the viewpoint of transparency.
[0041] The organic ultraviolet absorbent includes, but is not limited to, benzotriazole, benzophenone, cyclic imino ester, and the like, and any combination thereof.From the viewpoint of durability, benzotriazole or cyclic imino ester is particularly preferred.When two or more kinds of ultraviolet absorbents are used in combination, ultraviolet rays of different wavelengths can be absorbed simultaneously, so that ultraviolet absorption effect can be further improved.
[0042] Benzophenone-based ultraviolet absorbents, benzotriazole-based ultraviolet absorbents, and acrylonitrile-based ultraviolet absorbents include, for example, 2-[2'-hydroxy-5'-(methacrylonitrile) 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(5-chloro(2H)-benzyl) Examples of cyclic imino ester-based ultraviolet absorbents include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, and the like. These ultraviolet absorbents may be used alone or in combination of two or more.
[0043] When an ultraviolet absorbing agent is blended in a polyester film, it is preferable that the oriented polyester film has a multi-layer structure of three or more layers, and that the ultraviolet absorbing agent is added to a layer other than the outermost layer of the film (ie, an intermediate layer).
[0044] (Other ingredients, etc.) In addition to the ultraviolet absorber, it is also a preferred embodiment that the oriented polyester film contains various additives within a range that does not impair the effects of the present invention. Examples of additives include inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, gelling inhibitors, surfactants, etc. In addition, in order to achieve high transparency, it is also preferable that the polyester film does not substantially contain particles. "Substantially does not contain particles" means, for example, in the case of inorganic particles, that the content of inorganic elements is 50 ppm or less, preferably 10 ppm or less, and particularly preferably below the detection limit when the inorganic elements are quantified by fluorescent X-ray analysis.
[0045] (Easy adhesion layer) In the present invention, in order to improve the adhesion to the polarizer, it is preferable that at least one side of the polyester film has an easy-adhesion layer mainly composed of at least one of polyester resin, polyurethane resin, and polyacrylic resin. Here, the "main component" refers to a component that is 50% by mass or more of the solid components constituting the easy-adhesion layer. The coating liquid used to form the easy-adhesion layer is preferably an aqueous coating liquid containing at least one of water-soluble or water-dispersible copolymer polyester resin, acrylic resin, and polyurethane resin. Examples of these coating liquids include water-soluble or water-dispersible copolymer polyester resin solutions, acrylic resin solutions, and polyurethane resin solutions disclosed in Japanese Patent No. 3567927, Japanese Patent No. 3589232, Japanese Patent No. 3589233, Japanese Patent No. 3900191, Japanese Patent No. 4150982, etc.
[0046] The easy-adhesion layer can be obtained by applying the above-mentioned coating liquid to one or both sides of an unstretched film or a uniaxially stretched film in the machine direction, drying the film at 100 to 150°C, and further stretching the film in the transverse direction. The final coating amount of the easy-adhesion layer is 0.05 to 0.2 g / m 2 It is preferable to control the coating amount to 0.05 g / m 2 If the coating amount is less than 0.2 g / m, the adhesion to the obtained polarizer may be insufficient. 2When the easy-adhesion layer is provided on both sides of the polyester film, the coating amounts of the easy-adhesion layers on both sides may be the same or different, and each can be independently set within the above range.
[0047] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the coating layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.
[0048] The average particle size of particles can be obtained by taking photographs of the particles with a scanning electron microscope (SEM), measuring the maximum diameters (the distance between the two furthest points) of 300 to 500 particles at a magnification such that the smallest particle is 2 to 5 mm, and then calculating the average value.
[0049] The coating solution can be applied by a known method, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating. These methods can be used alone or in combination.
[0050] The polyester film may be subjected to corona treatment, coating treatment, flame treatment, or the like in order to improve adhesion to the polarizer.
[0051] (Functional layer) It is also a preferred embodiment that various functional layers, i.e., one or more functional layers selected from the group consisting of a hard coat layer, an antiglare layer, an antireflection layer, a low reflection layer, a low antireflection layer, an antireflection antiglare layer, and an antistatic layer, are provided on the oriented polyester surface for the purpose of preventing reflection, suppressing glare, suppressing scratches, etc., on the surface of the polyester film opposite to the surface on which the polarizer is disposed. When providing various functional layers, it is preferable that the oriented polyester film has an easy-adhesion layer on its surface. In this case, from the viewpoint of suppressing interference due to reflected light, it is preferable to adjust the refractive index of the easy-adhesion layer so that it is close to the geometric mean of the refractive index of the functional layer and the refractive index of the oriented polyester film. The refractive index of the easy-adhesion layer can be adjusted by adopting a known method, and can be easily adjusted, for example, by adding titanium, zirconium, or other metal species to the binder resin.
[0052] (Production method of polyester film) The polyester film used as the polarizer protective film can be manufactured according to a general method for manufacturing a polyester film. For example, a method can be mentioned in which a polyester resin is melted, and the non-oriented polyester extruded into a sheet is stretched in the longitudinal direction by utilizing the speed difference between rolls at a temperature equal to or higher than the glass transition temperature, and then the polyester is stretched in the transverse direction by a tenter and heat-treated. The film may be either a uniaxially stretched film or a biaxially stretched film.
[0053] (Reduction of thermal shrinkage rate gradient) There are no particular limitations on the means for controlling the absolute value of the gradient of the direction in which the thermal shrinkage rate is maximum relative to the film flow direction or width direction to 15 degrees or less, but it is preferable to pay attention to the following points. That is, in the cooling section after the heat treatment process in the tenter, there is shrinkage stress due to stretching that was not completely removed by heat setting and thermal stress due to cooling. In addition, since the film at the ends is restrained by clips while the film in the center is relatively expandable, there is a bias in the distribution of stress in the film flow direction and width direction in the cooling section. These are the main causes of the gradient in the thermal shrinkage rate. In light of these circumstances, specific means for reducing the gradient in the thermal shrinkage rate are exemplified below.
[0054] (Method 1 for reducing the thermal shrinkage rate gradient) In the cooling section after heat setting, the clip interval is narrowed in the film flow direction, and the stress in the film flow direction in the tenter cooling section can be made uniform, and the gradient of the thermal shrinkage rate can be reduced. Therefore, in order to reduce the gradient of the thermal shrinkage rate, it is preferable to appropriately adjust the temperature range for narrowing the clip interval. Since it varies depending on the film composition and the film manufacturing conditions, there is no particular limitation, but if the temperature is too high, the gradient of the thermal shrinkage rate of the film at the left end (when the film is viewed from above) in the flow direction increases in the positive direction (the gradient of the right end increases in the negative direction). In addition, if the temperature is too low, the amount of thermal shrinkage of the film is too small, resulting in poor flatness, which is not preferable. In this way, by setting the temperature for narrowing the clip interval within an appropriate range, the stress in the flow direction in the tenter cooling section can be made uniform, and the gradient of the thermal shrinkage rate can be reduced.
[0055] In order to reduce the gradient of the thermal shrinkage rate, the relaxation rate that narrows the clip interval in the film flow direction is also important. Since it varies depending on the film composition and film production conditions, there are no particular limitations, but the relaxation rate is preferably 0.01 to 3%, and more preferably 0.05 to 1.5%. If the relaxation rate is too high, the film does not shrink completely, resulting in poor flatness, which is not preferable. Also, if the relaxation rate is too low, the effect of reducing the gradient of the thermal shrinkage rate is reduced. The relaxation rate here can be calculated by the following formula using the center-to-center distance of the clips as shown in Figure 3. Relaxation rate = (((distance between clips before relaxation) - (distance between clips after relaxation)) / (distance between clips before relaxation)) x 100 (%) If the thermal shrinkage in the width direction is too high, the gradient of the thermal shrinkage tends to be large. Therefore, it is more preferable to adjust the tenter rail pattern and appropriately adjust the relaxation rate and temperature for narrowing the clip interval in the film width direction. In this way, by setting the temperature range and relaxation rate for narrowing the clip interval in the film flow direction in an appropriate range, and appropriately adjusting the tenter rail pattern as necessary so that the shrinkage in the width direction does not become too large, the stress in the flow direction in the tenter cooling section can be made uniform, and the gradient of the thermal shrinkage can be reduced.
[0056] (Method 2 for reducing the thermal shrinkage gradient) In the cooling section after heat setting, the film end is separated from the clip and released from the restraint by the clip, so that the stress in the width direction in the tenter cooling section can be made uniform. In addition, by adjusting the tension in the winding process to an appropriate value, the stress in the machine direction in the tenter cooling section can be made uniform. In this way, the gradient of the thermal shrinkage can be reduced by making the stress in the machine direction in the tenter cooling section uniform.
[0057] The method for separating the film end from the clip is not particularly limited, and may be a conventionally known method. Specifically, the method may include a method for cutting the film from the clip and a method for releasing the clip. The method for cutting the film from the grip is arbitrary, and may include, for example, cutting using a shear blade or melt cutting using a laser. These methods may also be combined. When cutting the film from the clip, it is desirable to cut the film at a position close to the clip on both ends of the film.
[0058] The film temperature when the film end is separated from the clip is preferably 50°C to 300°C. The higher the film temperature is relative to the film's melting point Tm, the more difficult it is to maintain the flatness of the film, and if the film temperature is too low relative to the film's glass transition temperature Tg, it becomes difficult to reduce the gradient of the thermal shrinkage rate. Therefore, it is preferable to cut and separate the film from the clip at a temperature higher than (glass transition temperature Tg-20°C) and lower than (melting point Tm-10°C). The film temperature here is a value measured by a radiation thermometer.
[0059] When the film end is separated from the clip, it is preferable to appropriately adjust the tension in the winding process. The appropriate tension varies depending on the film composition, thickness, and film production conditions, so is not particularly limited, but is 0.01 to 3 kg / mm 2 is preferable, and more preferably 0.1 to 2 kg / mm 2 If the tension is too high, the slope of the thermal shrinkage rate of the film at the left end relative to the flow direction will be greater in the positive direction (the slope at the right end will be greater in the negative direction). Also, if the tension is too low, the slope of the thermal shrinkage rate of the film at the left end relative to the flow direction will be greater in the negative direction (the slope at the right end will be greater in the positive direction). However, these trends are when the angle is evaluated based on the flow direction, and when the width direction is used as the standard, the positive and negative trends are reversed.
[0060] If the thermal shrinkage in the width direction is too high, the gradient of the thermal shrinkage becomes large. Therefore, it is preferable to adjust the rail pattern before the film end is separated from the clip, and adjust the relaxation rate and temperature to narrow the clip interval in the film width direction as described above. In this way, by setting the tension within an appropriate range, the stress in the flow direction in the tenter cooling section can be made uniform, and the gradient of the thermal shrinkage can be reduced.
[0061] (Method 3 for reducing the thermal shrinkage rate gradient) In the same way as in Reduction Method 2, the gradient of the heat shrinkage can also be reduced by setting the film temperature at the tenter outlet higher than a predetermined temperature (i.e., glass transition temperature Tg-20°C) and lower than a predetermined temperature (melting point Tm-70°C). In this case, since the effect depends on the room temperature, it is desirable to control the room temperature.
[0062] (Method 4 for reducing the thermal shrinkage rate gradient) The gradient of the thermal shrinkage rate can also be reduced by adjusting the temperature setting in the cooling process after the tenter heat setting. For example, as shown in FIG. 4, it is preferable to set the heat setting temperature to the tenter outlet temperature to be -15 / X to -100 / X (°C / m) along the tenter longitudinal direction. Here, X represents the tenter outlet width (m). Therefore, for example, when the tenter outlet width is 2 m, it is preferable to lower the temperature in the range of -7.5°C to -50°C for every 1 m in the tenter longitudinal direction. The above temperature indicates the temperature per tenter outlet width, and hereinafter, this is referred to as the temperature setting per unit width.
[0063] In addition, it is usually preferable to set the tenter outlet temperature below Tg. When the temperature setting per unit width is -100 / X (℃ / m) or less in the longitudinal direction, the gradient of the thermal shrinkage rate exceeds 15 degrees. If the thermal shrinkage rate is -15 / X(℃ / m) or more, the thermal shrinkage rate gradient is not sufficiently reduced. Although it is possible, it is not preferable because the investment in tenter equipment would be excessive.
[0064] (Method 5 for reducing the thermal shrinkage gradient) Even in the case of a film having a gradient in the thermal shrinkage rate, the gradient in the thermal shrinkage rate can be reduced by subjecting the roll once wound to offline annealing treatment, for example, at 80°C to 120°C, for 10 seconds to 90 minutes. In the case of offline annealing treatment, it is preferable to sufficiently secure and adjust the temperature and time of the annealing treatment. It is also preferable to perform an in-line annealing treatment between the exit of a tenter and a winding roll, which is known in the art. In this case, it is also preferable to sufficiently secure the temperature and time of the annealing treatment, as in the case of the above offline annealing treatment, and it is more preferable to use an air can roll in terms of heat treatment efficiency and maintenance of flatness.
[0065] These reduction methods 1 to 5 may be carried out alone or in combination. By these methods, the slope of the thermal shrinkage rate can be reduced to 15 degrees or less.
[0066] After being stretched longitudinally and transversely, the polyester film is subjected to a heat treatment process, and then both edges are cut off to form a mill roll, which is then slit as necessary to form a slit roll. The length of the entire width of the film is taken as 100%, and the range from both ends of the film is preferably 1% to 10%, and more preferably 1% to 5%. The both ends here are the same as the both ends of the film before cutting described in the above reduction method 2. Of these, the regions on both sides when the mill roll is divided into three equal parts tend to have particularly large absolute values of the gradient of the thermal shrinkage rate, so it is preferable to control the absolute value of the gradient of the thermal shrinkage rate in this region to 15 degrees or less.
[0067] The oriented polyester film having the specific retardation and Nz coefficient described above can be obtained by adjusting the film-forming conditions (e.g., stretching ratio, stretching temperature, film thickness, etc.). For example, the higher the stretching ratio, the lower the stretching temperature, and the thicker the film, the easier it is to obtain a high retardation. On the other hand, the lower the stretching ratio, the higher the stretching temperature, and the thinner the film, the easier it is to obtain a low retardation.
[0068] Specific film-forming conditions include, for example, a longitudinal stretching temperature and a transverse stretching temperature of preferably 80 to 145° C., more preferably 90 to 140° C. A longitudinal stretching ratio is preferably 1.0 to 3.5 times, more preferably 1.0 to 3.0 times, and a transverse stretching ratio is preferably 2.5 to 6.0 times, more preferably 3.0 to 5.5 times.
[0069] In order to control the retardation to the above-mentioned specific range, it is preferable to control the ratio of the longitudinal stretching ratio to the transverse stretching ratio. If the difference between the longitudinal and transverse stretching ratios is too small, it becomes difficult to increase the retardation, which is not preferable. In order to increase the retardation, it is also preferable to set the stretching temperature low. The temperature of the subsequent heat treatment is preferably 100 to 250°C, more preferably 180 to 245°C.
[0070] In order to set the Nz coefficient to the above-mentioned specific value, it is preferable to control the ratio of the longitudinal stretching ratio to the transverse stretching ratio, and it is preferable to make a uniaxially stretched film. In addition, in order to lower the Nz coefficient, it is also preferable to increase the molecular weight of the polymer and add a copolymerization component to lower the crystallinity. Furthermore, in order to control the Nz coefficient of the film to a specific range, it can be done by appropriately setting the total stretching ratio and the stretching temperature. For example, the lower the total stretching ratio and the higher the stretching temperature, the lower the Nz coefficient can be obtained.
[0071] In order to set the degree of planar orientation to the above-mentioned specific value, it is preferable to control the total stretching ratio. If the total stretching ratio is too high, the degree of planar orientation becomes too high, which is not preferable. It is also preferable to control the stretching temperature in order to reduce the degree of planar orientation. By increasing the difference between the longitudinal stretching ratio and the transverse stretching ratio, setting the total stretching ratio low, and setting the stretching temperature high, it is possible to set the Nz coefficient and the degree of planar orientation to a specific value or less.
[0072] Since the stretching temperature and stretching ratio have a large effect on the thickness unevenness of the film, it is preferable to optimize the film-forming conditions from the viewpoint of the thickness unevenness. In particular, if the longitudinal stretching ratio is reduced in order to increase the retardation, the longitudinal thickness unevenness may worsen. Since the longitudinal thickness unevenness becomes extremely worse in a certain range of the stretching ratio, it is preferable to set the film-forming conditions outside this range.
[0073] The ultraviolet absorbent can be incorporated into the oriented polyester film by combining known methods, for example, by using a kneading extruder to blend the dried ultraviolet absorbent with a polymer raw material to prepare a master batch in advance, and then mixing the master batch and the polymer raw material during film formation.
[0074] The concentration of the ultraviolet absorber in the master batch is preferably 5 to 30% by mass in order to disperse the ultraviolet absorber uniformly and to compound economically. The conditions for preparing the master batch are as follows: a kneading extruder is used, the extrusion temperature is the melting point of the polyester raw material or higher, and 290°C. It is preferable to extrude for 1 to 15 minutes at a temperature below 290°C. At 290°C or higher, the weight loss of the UV absorbent is large, and the viscosity of the master batch is significantly reduced. If the extrusion is performed for less than 1 minute, it becomes difficult to uniformly mix the UV absorbent. At this time, a stabilizer, a color tone adjuster, and an antistatic agent may be added as necessary.
[0075] The blending of an ultraviolet absorber into the intermediate layer of an oriented polyester film having a multi-layer structure of three or more layers can be carried out by the following method. For the outer layer, polyester pellets alone, and for the intermediate layer, a master batch containing an ultraviolet absorber and polyester pellets are mixed in a predetermined ratio, dried, and then fed to a known melt lamination extruder, extruded into a sheet from a slit die, and cooled and solidified on a casting roll to produce an unstretched film. That is, using two or more extruders, a three-layer manifold or a merging block (e.g., a merging block having a square merging portion), the film layers constituting both outer layers and the film layer constituting the intermediate layer are laminated, and the three-layer sheet is extruded from a die and cooled on a casting roll to produce an unstretched film.
[0076] In order to remove foreign matter contained in the raw polyester that causes optical defects, it is preferable to perform high-precision filtration during melt extrusion in the manufacturing process of oriented polyester film. The filtration particle size (initial filtration efficiency 95%) of the filter medium used for high-precision filtration of molten resin is preferably 15 μm or less. If the filtration particle size of the filter medium exceeds 15 μm, the removal of foreign matter of 20 μm or more is likely to be insufficient.
[0077] 1. Polarizing plate The polarizing plate is configured by sandwiching a polarizer made of a polyvinyl alcohol-based film dyed with iodine or the like between two polarizer protective films, and at least one of the two polarizer protective films is preferably a polyester film having a thermal shrinkage gradient absolute value within a specific range. In one embodiment, the polarizing plate is preferably configured by laminating a polarizer protective film on one surface of the polarizer. The polarizer and the polarizer protective film are laminated via an adhesive, and are usually heat-treated at a temperature in the range of 70°C to 120°C for about 10 to 60 minutes to obtain a polarizing plate.
[0078] (Polarizer protection film placement) In a liquid crystal display device, the specific polyester film is preferably used as both polarizer protective films of a pair of polarizing plates. A pair of polarizing plates means a combination of a polarizing plate arranged on the incident light side of the liquid crystal and a polarizing plate arranged on the outgoing light side of the liquid crystal. That is, the polyester film is preferably used for both the polarizing plate on the incident light side and the polarizing plate on the outgoing light side. The polyester film may be laminated on at least one surface of the polarizer constituting each polarizing plate.
[0079] In a preferred embodiment, the polyester film is used as a polarizer protective film on the incident light side of the polarizing plate on the incident light side, and is used as a polarizer protective film on the exit light side of the polarizing plate on the exit light side. When the oriented polyester film is laminated only on one side of the polarizer constituting the polarizing plate, any polarizer protective film (e.g., TAC film, etc.) can be used on the other side, or a polarizer protective film can be not provided. If the polyester film is adopted as the polarizer protective film on the liquid crystal cell side of the polarizing plate arranged on the incident light side and the polarizer protective film on the liquid crystal cell side (i.e., the incident light side) of the polarizing plate arranged on the exit light side, the polarization characteristics of the liquid crystal cell may be changed, so it is preferable to use a polarizer protective film other than the polyester film (e.g., a film without birefringence such as a TAC film, an acrylic film, or a norbornene-based film) as the polarizer protective film at these positions. It is also preferable that the absolute value of the slope of the thermal shrinkage rate of these films is small.
[0080] 2.Liquid crystal display device In general, a liquid crystal display device is composed of a rear module, a liquid crystal cell, and a front module, in that order from the side facing the backlight light source toward the side where an image is displayed (the viewing side or the light output side). The rear module and the front module are generally composed of a transparent substrate, a transparent conductive film formed on the liquid crystal cell side surface, and a polarizing plate arranged on the opposite side. Here, the polarizing plate is arranged on the side facing the backlight light source in the rear module, and on the side where an image is displayed (the viewing side or the light output side) in the front module.
[0081] (Backlight source) The liquid crystal display device includes at least a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates as components. The liquid crystal display device of the present invention may include other components, such as a color filter, a lens film, a diffusion sheet, and an anti-reflection film, as appropriate.
[0082] The backlight may be of an edge light type having a light guide plate, a reflector, or a direct type. The backlight light source is preferably a white light source having a continuous and wide emission spectrum. Here, the continuous and wide emission spectrum means an emission spectrum in which there is no wavelength at which the light intensity is zero in at least the wavelength region of 450 nm to 650 nm, preferably in the visible light region. An example of a white light source having such a continuous and wide emission spectrum is a white LED, but is not limited thereto.
[0083] The white LEDs that can be used in the present invention include phosphor-based elements that emit white light by combining a light-emitting diode that emits blue light or ultraviolet light using a compound semiconductor with a phosphor, and organic light-emitting diodes (OLEDs). Examples of phosphors include yttrium-aluminum-garnet-based yellow phosphors and terbium-aluminum-garnet-based yellow phosphors. Among white LEDs, a white light-emitting diode consisting of a light-emitting element that combines a blue light-emitting diode using a compound semiconductor with a yellow phosphor of yttrium-aluminum-garnet has a continuous and wide emission spectrum and is excellent in luminous efficiency, and is therefore suitable as a backlight source for the present invention. Since white LEDs consume little power, the liquid crystal display device of the present invention that uses them also contributes to energy saving.
[0084] Fluorescent tubes such as cold cathode fluorescent tubes and hot cathode fluorescent tubes, which have been widely used as backlight light sources, have a discontinuous emission spectrum with a peak at a specific wavelength, and therefore it is difficult to achieve the effect of suppressing rainbow spots, and therefore they are not preferable as the light source for the liquid crystal display device of the present invention. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the spirit of the present invention, all of which are included in the technical scope of the present invention.
[0086] The physical properties in the examples were evaluated as follows. (1) Thermal shrinkage rate and its slope The polyester film cut from each cut-out section of the slit roll was cut into a square shape with sides of 21 cm, and left for 2 hours or more in an atmosphere of 23°C and 65% RH. A circle with a diameter of 80 mm was drawn with the center of the polyester film as the center, and the circle was measured using a two-dimensional image measuring device (MIT Using a QUICK IMAGE (UTOYO), the diameter was measured at 5-degree intervals with the film flow direction set to 0 degrees. Here, the film flow direction was set to 0 degrees, and the clockwise (right-handed) angle was set as a positive angle on the upper surface of the film, and the counterclockwise (left-handed) angle was set as a negative angle. Since the diameter was measured, it was measured in all directions in the range of -90 degrees to 85 degrees. Next, this polyester film was heat-treated in water at 85°C for 30 minutes, and then the moisture adhering to the film surface was wiped off, and the film was air-dried and left in an atmosphere of 23°C and 65% RH for 2 hours or more. Thereafter, the diameter of the circle was measured at 5-degree intervals in the same manner as above. The diameter before heat treatment was Lo, and the diameter in the same direction after heat treatment was L, and the heat shrinkage rate in each direction was calculated according to the following formula.
[0087] Heat shrinkage rate (%) = ((L0- L) / L0) x 100
[0088] (Maximum heat shrinkage rate) The maximum value of the heat shrinkage rates in all directions is defined as the maximum heat shrinkage rate. For each slit roll (L, C, R), three points were sampled in the film width direction (three points at the center and both ends) and similar evaluation was performed, and the average of the three maximum heat shrinkage rates was recorded as the maximum heat shrinkage rate in Table 1. In this example, the maximum heat shrinkage rate was 5% or less at the three points at the center and both ends for all of the slit rolls.
[0089] (Reading the maximum direction of thermal shrinkage (α)) From the results of the thermal shrinkage in all directions, the gradient of the thermal shrinkage was calculated as follows. The measured values (-90 degrees to 85 degrees) were plotted as shown in Figure 2, with the horizontal axis representing the angle and the vertical axis representing the thermal shrinkage corresponding to that angle, and the values from -180 degrees to -95 degrees and 90 degrees to 175 degrees were interpolated. A heat shrinkage rate of 0 degrees corresponds to a heat shrinkage rate of 90 degrees, and a heat shrinkage rate of 0 degrees corresponds to a heat shrinkage rate of -180 degrees.) Next, an approximation curve was drawn connecting the plots, and the direction in which the heat shrinkage rate is maximum was read with an accuracy of 1 degree and defined as α. However, -90 degrees ≦ α ≦ 90 degrees.
[0090] (Thermal shrinkage rate gradient) When the direction α in which the thermal shrinkage is maximum is in the range of -45 degrees to 45 degrees, the value was taken as the gradient of the thermal shrinkage. When the direction α in which the thermal shrinkage is maximum is 45 degrees or more and -45 degrees or less, it is understood that the gradient is based on the film width direction, not the film flow direction, and α-90 degrees (when α is 45 degrees or more) and 90 degrees + α (when α is -45 degrees or less) were taken as the gradient of the thermal shrinkage. The above measurements were similarly performed for each slit roll (L, C, R) by sampling three points (three points at the center and both ends) in the film width direction, and the average of the absolute values of the gradients of the three thermal shrinkages was listed in Table 1 as the gradient of the thermal shrinkage. In this example, the absolute values of the gradients of the thermal shrinkages at the three points at the center and both ends were 15 degrees or less.
[0091] (2) Light leakage evaluation method A triacetyl cellulose film (Fujifilm) is attached to one side of the polarizer made of PVA film. A polyester film (manufactured by JASCO Corporation, thickness 80 μm) was laminated on one side, and a polyester film prepared by the method described below was laminated on the other side. An adhesive was used for lamination, and the laminate was heated in an oven at 85° C. for 30 minutes to produce a polarizing plate. The laminate was laminated so that the polarization axis of the polarizer and the main orientation axis of the polyester film were perpendicular to each other. The two polarizing plates thus obtained were arranged in a crossed Nicol position. At this time, the two polarizing plates were arranged so that each polyester film was located outside the polarizer. Then, the maximum light transmittance of light with a wavelength of 550 nm to 600 nm that was transmitted through the two polarizing plates was measured using a spectrophotometer V7100 manufactured by JASCO. The measurement results were evaluated as follows. ○: Maximum light transmittance is 0.02% or less ×: Maximum light transmittance is 0.02% or more
[0092] (3) Retardation (Re) Retardation is a parameter defined by the product (ΔNxy×d) of the refractive index anisotropy of two orthogonal axes on a film (ΔNxy=|nx-ny|) and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔNxy) was determined by the following method. The orientation axis direction of the film was determined using a molecular orientation meter (MOA-6004 type molecular orientation meter, manufactured by Oji Measurement Instruments Co., Ltd.), and a rectangle of 4 cm×2 cm was cut out so that the orientation axis direction was the long side, and used as a measurement sample. The refractive indexes (nx, ny) of the two orthogonal axes and the refractive index (Nz) in the thickness direction of this sample were measured using an Abbe refractometer (NAR-4T, manufactured by Atago Co., Ltd., measurement wavelength 589 nm), and the absolute value of the difference between the refractive indices of the two axes (|nx-ny|) was taken as the refractive index anisotropy (ΔNxy). The film thickness d (nm) was measured using an electric micrometer (Militron 1245D, Fineluf Co., Ltd.) and converted into units of nm. The retardation (Re) was calculated from the product (ΔNxy×d) of the refractive index anisotropy (ΔNxy) and the film thickness d (nm).
[0093] (4) Nz coefficient The value obtained by |ny-nz| / |ny-nx| was used as the Nz coefficient, where the values of ny and nx were selected so that ny>nx.
[0094] (5) Degree of plane orientation (△P) The value obtained by (nx+ny) / 2-nz was defined as the degree of planar orientation (△P).
[0095] (6) Thickness retardation (Rth) The thickness retardation is a parameter that indicates the average retardation obtained by multiplying the two birefringences ΔNxz (=|nx-nz|) and ΔNyz (=|ny-nz|) when viewed from the cross section of the film thickness direction by the film thickness d. nx, ny, nz and the film thickness d (nm) were obtained in the same manner as in the retardation measurement, and the average value of (ΔNxz×d) and (ΔNyz×d) was calculated to obtain the thickness retardation (Rth).
[0096] (7) Iridescence observation A polyester film prepared by the method described below was attached to one side of a polarizer made of PVA and iodine so that the polarization axis of the polarizer and the orientation axis of the polyester film were perpendicular, and a TAC film (manufactured by Fuji Film Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate. The obtained polarizing plates were arranged on both sides of the liquid crystal so that the polarizing plates were in a cross-Nicol relationship, and a liquid crystal display device was prepared. Each polarizing plate was arranged so that the polyester film was on the opposite side (distal) to the liquid crystal. A white LED (Nichia Chemical, NSPW500CS) consisting of a light-emitting element combining a blue light-emitting diode and a yttrium-aluminum-garnet yellow phosphor was used as the light source for the liquid crystal display device. The liquid crystal display device was visually observed from the front and oblique directions, and the occurrence of rainbow spots was judged as follows. A: No rainbow spots observed from any direction. A': When observed from an oblique direction, very faint rainbow spots can be observed depending on the angle. B: When observed from an oblique direction, faint rainbow spots can be seen depending on the angle. C: Rainbow spots are observed when observed from an oblique angle. D: Iridescence is observed when observed from the front and at an angle.
[0097] (8) Tear strength The tear strength of each film was measured according to JIS P-8116 using an Elmendorf tear tester manufactured by Toyo Seiki Seisakusho. The tear direction was parallel to the main orientation axis direction of the film, and the results were judged as follows. The main orientation axis direction was measured using a molecular orientation meter (MOA-6004 molecular orientation meter manufactured by Oji Keisokuki Co., Ltd.).
[0098] ○: Tear strength is 50mN or more ×: Tear strength is less than 50 mN
[0099] (Production Example 1-Polyester A) When the temperature of the esterification reactor reached 200°C, 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol were charged, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were charged as catalysts while stirring. Next, the temperature was increased under pressure and a pressure esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C, after which the esterification reactor was returned to normal pressure and 0.014 parts by mass of phosphoric acid was added. Further, the temperature was increased to 260°C over 15 minutes, and 0.012 parts by mass of trimethyl phosphate was added. Next, after 15 minutes, a dispersion treatment was carried out using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor and a polycondensation reaction was carried out under reduced pressure at 280°C.
[0100] After the polycondensation reaction was completed, the mixture was filtered using a Naslon filter with a 95% cut diameter of 5 μm, extruded from a nozzle in the form of a strand, cooled and solidified using cooling water that had been previously filtered (pore diameter: 1 μm or less), and cut into pellets. The intrinsic viscosity of the resulting polyethylene terephthalate resin (A) was 0.62 dl / g, and it contained substantially no inert particles or internally precipitated particles. (Hereinafter, this will be abbreviated as PET (A)).
[0101] (Production Example 2 - Polyester B) 10 parts by mass of dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of particle-free PET (A) (intrinsic viscosity 0.62 dl / g) were mixed and kneaded using an extruder to obtain polyethylene terephthalate resin (B) containing an ultraviolet absorber (hereinafter referred to as PET (B)).
[0102] (Production Example 3 - Preparation of Adhesion Modifier Coating Solution) A water-dispersible sulfonate metal base-containing copolymerized polyester resin was prepared by carrying out an ester exchange reaction and a polycondensation reaction in a conventional manner, in which the dicarboxylic acid component is 46 mol% terephthalic acid, 46 mol% isophthalic acid, and 8 mol% sodium 5-sulfonatoisophthalate (relative to the total dicarboxylic acid component), and the glycol component is 50 mol% ethylene glycol and 50 mol% neopentyl glycol (relative to the total glycol component). Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve, and 0.06 parts by mass of a nonionic surfactant were mixed, heated and stirred, and when the temperature reached 77°C, 5 parts by mass of the water-dispersible sulfonate metal base-containing copolymerized polyester resin was added, and the mixture was stirred until no resin lumps remained, and then the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolymerized polyester resin liquid with a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of aggregated silica particles (manufactured by Fuji Silysia Co., Ltd., Sylysia 310) were dispersed in 50 parts by mass of water, and then 0.54 parts by mass of the aqueous dispersion of Sylysia 310 was added to 99.46 parts by mass of the above water-dispersible copolymer polyester resin liquid, and 20 parts by mass of water was added while stirring to obtain an adhesion-modifying coating liquid.
[0103] (Polarizer protection film 1) As the raw material for the intermediate layer of the base film, 90 parts by mass of PET (A) resin pellets containing no particles and 10 parts by mass of PET (B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135 ° C for 6 hours, and then fed to extruder 2 (for intermediate layer II). PET (A) was also dried by a conventional method and fed to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285 ° C. These two types of polymers were each filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particle 95% cut) and laminated in a two-type three-layer merging block, extruded into a sheet shape from a die, and then wrapped around a casting drum with a surface temperature of 30 ° C. using an electrostatic casting method, cooled and solidified, and an unstretched film was made. At this time, the I layer, II layer, The discharge rates of the extruders were adjusted so that the thickness ratio of the III layers was 10:80:10.
[0104] Next, the unstretched PET film was coated on both sides with a 0.08 g / m coating after drying by the reverse roll method. 2 After the adhesiveness-modifying coating liquid was applied so that the thickness became 100 μm, the coating was dried at 80° C. for 20 seconds.
[0105] The unstretched film with the coating layer formed thereon was introduced into a tenter stretching machine, and while the ends of the film were held by clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 4.0 times in the width direction. Next, while maintaining the width stretched in the width direction, the film was treated at a temperature of 225°C for 30 seconds, and then cooled to 130°C. The film was cut with a shear blade at a position 2% from both ends and stretched at a pressure of 0.5 kg / mm 2 The roll was wound up with a tension of 0.01 mm and both edges were cut and removed to obtain a mill roll made of uniaxially oriented PET film with a thickness of approximately 50 μm. This mill roll was divided into thirds to obtain three slit rolls (L, C, R). The slit roll located on the left side of the film flow direction was designated L, the slit roll located on the right side was designated R, and the central roll was designated C.
[0106] (Polarizer protection film 2) Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as in the polarizer protective film 1, except that the thickness of the unstretched film was changed to about 100 μm.
[0107] (Polarizer protection film 3) Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as in Polarizer Protective Film 1, except that the film was not cut with a shear blade after heat setting.
[0108] (Polarizer protection film 4) An unstretched film produced in the same manner as for Polarizer Protective Film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched twice in the running direction using a group of rolls having different peripheral speeds. The film was then stretched 4.0 times in the width direction using the same method as for Polarizer Protective Film 1, and the film was then cooled to 140°C. The film was then cut at positions 2% from both ends with a shear blade and subjected to a cutting force of 0.65 kg / mm 2The unstretched film was wound up with a tension of 0.01 mm and the thickness of the unstretched film was adjusted to obtain three slit rolls (L, C, R) of biaxially oriented PET film with a film thickness of approximately 50 μm.
[0109] (Polarizer protection film 5) Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as polarizer protective film 1, except that the method for separating the film from the clip was changed from cutting with a shear blade to releasing the clip.
[0110] (Polarizer protection film 6) Using the same method as for polarizer protective film 1, the film was stretched 1.0 times in the running direction and 3.5 times in the width direction to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of about 75 μm.
[0111] (Polarizer protection film 7) Using the same method as for polarizer protective film 1, the thickness of the unstretched film was changed, the transverse stretching ratio was 3.8 times, and the stretching temperature was 135°C, to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a thickness of approximately 100 μm.
[0112] (Polarizer protection film 8) The film was stretched in the same manner as in the polarizer protective film 1, but the transverse stretching ratio was 3.8 times and the stretching temperature was 135°C. C., and three slit rolls (L, C, R) made of uniaxially oriented PET film with a thickness of approximately 50 μm were obtained.
[0113] (Polarizer protection film 9) Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as in Polarizer Protective Film 8, except that the film was not cut with a shear blade after heat setting.
[0114] (Polarizer protection film 10) Using the same method as for Polarizer Protective Film 1, the transverse stretching ratio was set to 4.2 times and the stretching temperature was set to 135° C. to obtain three slit rolls (L, C, R) made of a uniaxially oriented PET film with a thickness of about 50 μm.
[0115] (Polarizer protection film 11) Winding tension after cutting with shear blade is 0.2kg / mm 2 Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as for Polarizer Protective Film 10, except that the above-mentioned procedure was followed.
[0116] (Polarizer protection film 12) Three slit rolls (L, C, R) made of uniaxially oriented PET film were obtained in the same manner as for Polarizer Protective Film 10, except that the film was not cut with a shear blade after heat setting.
[0117] (Polarizer protection film 13) Using the same method as for polarizer protective film 4, the film was stretched 1.8 times in the running direction and 2.0 times in the width direction, and then cut with a shear blade and wound under a tension of 0.2 kg / mm 2 Three slit rolls (L, C, R) of biaxially oriented PET film with a film thickness of approximately 275 μm were obtained.
[0118] (Polarizer protection film 14) An unstretched film prepared in the same manner as polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds, and the clip spacing was narrowed by 0.2% in the machine direction in the temperature range of 90°C to 70°C, to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0119] (Polarizer protection film 15) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds, and the clip spacing was narrowed by 0.1% in the machine direction in the temperature range of 90°C to 70°C to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0120] (Polarizer protection film 16) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds, and the clip spacing was narrowed by 0.2% in the machine direction in the temperature range of 110°C to 70°C to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0121] (Polarizer protection film 17) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds, and the clip spacing was narrowed by 0.4% in the machine direction in the temperature range of 150°C to 100°C to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0122] (Polarizer protection film 18) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds and cooled at a temperature setting of -55°C / m per unit width to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0123] (Polarizer protection film 19) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds and cooled with a temperature setting of -35°C / m per unit width to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0124] (Polarizer protection film 20) An unstretched film prepared in the same manner as for polarizer protective film 1 was introduced into a tenter stretching machine, and while the ends of the film were held with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 3.5 times in the width direction. Next, while maintaining the stretched width in the width direction, it was treated at a temperature of 225°C for 30 seconds and cooled with a temperature setting of -120°C / m per unit width to obtain three slit rolls (L, C, R) made of uniaxially oriented PET film with a film thickness of approximately 75 μm.
[0125] For the polarizer protective films 1 to 20, the absolute value of the slope of the heat shrinkage rate, the maximum value of the heat shrinkage rate, and the results of the light leakage evaluation are shown in Table 1.
[0126] [Table 1]
[0127] In Table 1, "film" refers to the above polarizer protective film.
[0128] Furthermore, for the liquid crystal displays produced as described above using the Polarizer Protective Films 1 to 20, rainbow spots were observed and the tear strength was measured. The results are shown in Table 2 below.
[0129] [Table 2]
[0130] The results shown in Table 1 indicate that if the absolute value of the gradient of the thermal shrinkage is 15 degrees or less, slight light leakage can be suppressed when two polarizing plates are arranged in a crossed Nicol relationship. In addition, the maximum thermal shrinkage of the polarizer protective films 1 to 20 was all less than 1%.
[0131] The results shown in Table 2 show that when the retardation of the oriented polyester film is 4000 or more and the Nz coefficient is 1.7 or less, the occurrence of rainbow spots is significantly suppressed. In addition to these conditions, when the plane orientation degree of the oriented polyester film is 0. It was shown that by controlling the ratio of 13 to 13, it is possible to more effectively suppress the occurrence of iridescence. [Industrial Applicability]
[0132] According to the present invention, when two polarizing plates are arranged in a crossed Nicol relationship, it is possible to provide a polarizer protective film made of a polyester film suitable for obtaining a liquid crystal display device having excellent visibility by suppressing the occurrence of slight light leakage. Therefore, the industrial applicability of the present invention is extremely high.
Claims
1. the absolute value of the inclination of the direction in which the thermal shrinkage rate (thermal shrinkage rate when heated in water at 85° C. for 30 minutes) is maximum with respect to the machine direction or width direction of the film is 15° or less; a polyester film having a difference between the maximum and minimum heat shrinkage rates of more than 0.1% when measured over 360 degrees at 5 degree intervals; The retardation of the polyester film is 4000 nm or more and 30000 nm or less, the Nz coefficient is 1.7 or less, and the degree of planar orientation is 0.117 or more and 0.130 or less. Polarizer protection film.
2. The polarizer protective film according to claim 1 , wherein the maximum heat shrinkage rate is 1% or less.
3. The polarizer protective film according to claim 1 , further comprising an easy-adhesion layer on at least one surface of the polyester film.
4. A polarizing plate comprising the polarizer protective film according to any one of claims 1 to 3 and a polarizer.
5. A liquid crystal display device comprising: a backlight source; two polarizing plates according to claim 4; and a liquid crystal cell disposed between the two polarizing plates; The two polarizing plates are in a crossed Nicol relationship. LCD display device.
Citation Information
Patent Citations
Electrolytic refining method of nickel
JP1982054290A
Optical film, polarizing plate using the same, method for producing the same and liquid crystal display
JP2002116320A
Polarizing plate and its manufacturing method, and liquid crystal display device using the same
JP2004205773A
Polarizing plate protective film, and polarizing plate and liquid crystal display device using the same,
JP2004219620A
Biaxially oriented laminated polyester film
JP2010046817A
Cited By
Polarizer protective film, polarizing plate, and liquid crystal display device
JP2024045417A